O princípio do contraditório no Código de Processo Civil de 2015 - Sales Junior, Reinaldo Paulo (2023)
This dissertation aimed to investigate whether the changes brought by the Civil Procedure Code of 2015 (CPC/2015) were sufficient to ensure a substantial contradictory and, consequently, give greater quality to judicial decisions. The objective was to discuss the adversarial principle with the advent of CPC/2015. To this end, from a perspective of the Social Democratic State, the Rule of Law and the constitutional process model, the dissertation sought to understand the aforementioned principle, especially with the changes implemented by the CPC/2015; discussed the construction of a democratic process based on the adversarial principle; analyzed the incidence of the contradictory in different moments of the process; and exposed some aspects considered relevant about the contradictory in CPC/2015. The research allowed us to understand that the contradictory, initially understood as the binomial information- reaction, evolved into the trinomial information-reactionparticipation, that is, necessary information, possible reaction and guaranteed participation (right not to be surprised). Thus, it was concluded that the contradictory, seen as a symmetric and equal participation of the parties in the process, within the list of fundamental rights and guarantees that emanate from the Federal Constitution of 1988, underwent a mutation that, without disregarding its formal dimension (bilateral hearing) , incorporated a substantial dimension (isonomic treatment and the possibility for the parties to influence judicial decisions) at the beginning, which is positive, guaranteeing greater legal certainty to the parties due to the better quality of the substantive adversary